Carbachol stimulation of gastric acid secretion and its effects on the parietal cell - Sandvik, Arne K (1998)
1. The acid secretagogue effect of gastrin is mainly mediated by the release of enterochromaffin-like (ECL) cell histamine, but the mechanism of muscarinic stimulation of acid secretion remains unclear. The results of studying aminopyrine uptake in isolated parietal cells, and histamine release in isolated ECL cells suggest that muscarinic agents may act both directly on the parietal cell and indirectly via histamine release from ECL cells. 2. We examined parietal and ECL cell responses to the muscarinic agent carbamylcholine (carbachol) in conscious rats and in rat isolated vascularly perfused stomachs. 3. Intravenous carbachol stimulated acid secretion in conscious gastric fistula rats and increased H(+)K(+) ATPase mRNA abundance, indicating activation of parietal cells. In these experiments there was no increase in portal venous histamine, or in oxyntic mucosal histidine decarboxylase (HDC) enzyme activity and HDC mRNA abundance. 4. In rat isolated stomachs stimulated with carbachol in the dose range 10 nM–1 mM only the 1 μM concentration increased venous histamine significantly. 5. We concluded that the muscarinic agent carbachol stimulates acid secretion and H(+)K(+) ATPase mRNA in vivo by a direct effect on the parietal cell, that does not depend on the release of ECL cell histamine.